A relação família escola: existe um culpado na queixa escolar? - Fantinato, Fernanda Golghetto (2012)
Complains originating from school counselors have been studied by Psychology for many years. Initially it was thought that the student was to blame being the only one responsible for his/her difficulty and that the problem was biological and psychological in origin. After that, theories were developed which blamed the families and the problem was social and economic in origin. The school system itself was the last link to be theorized upon as responsible for the difficulties presented by the students. Despite the fact that the relationship between the school and the family is an important factor in the genesis of learning difficulties there has been no actual productive communication between these two institutions. This way of theorizing upon school complaints makes families seek psychological counseling for their sons and daughters. Considering the families and the school of a country city in the state of São Paulo, in an interconnected manner and having a global outlook about school complaints, this research tried to understand the relation between the school and the family and look for a different manner of perceiving the child´s difficulty, in a way that won´t seek a guilty party. To achieve such goal semi-structured interviews were conducted with the families and the school, qualitatively analyzed interpreting the contents of the participants. We found stereotyped views, which make a clear dialogue difficult between school and family and are detrimental to the student and cause feelings of helplessness in the families who start believing they are incapable of helping their child at school. A clearer dialogue would be necessary for the setting of a more productive development environment for the child and his/her learning process